A novel CWDM bearer scheme for 5G fronthaul network - Ming CHENG; Zhe DU; Dezhi ZHANG (Dianxin kexue)
With the rapid growth of 5G network traffic, the bearer requirement for 6-channel 25 Gbit/s fronthaul has become increasingly obvious.The main schemes and standardizations of fronthaul technology in the existing network were introduced.A novel bearer scheme based on CWDM and optical circulator to satisfy the requirements for 6-channel 25 Gbit/s fronthaul with low cost was proposed.The advantages and challenges of the scheme were analyzed.Tests in laboratory and pilots in actual network were introduced.